MENINGKATKAN PEMAHAMAN KONSEP MAHASISWA CALON GURU SEKOLAH DASAR PADA MATERI FLUIDA STATIS DENGAN GAME ANDROID - Muhammad Erfan; Arif Widodo (IKIP Siliwangi, 2021)
This study aims to improve understanding of the concept of prospective elementary school teacher students on static fluid material assisted by android games. The Android game used is Water Physics Simulation. This research is a quasi-experimental study with the samples used are class 5E as the experimental class and class 5H as the control class. The experimental class learns the concepts of static fluid with the help of Android games and the control class learns the concepts of static fluid as usual, namely conventionally (lectures via webmeeting). Data regarding the understanding of the concept of static fluid for elementary school teacher candidates were obtained by tests (pretest and posttest) which were then analyzed by independent sample t-test and normalized gain test. The results showed that the experimental class after being given treatment had a higher understanding of the static fluid concept than the control class. So, from this study it was found that the Android Water Physics Simulation Game was effective in improving the understanding of the concept of static fluid for elementary school teacher candidates.